Land-Use Change Scenarios and Their Implications for Bird Conservation in Subtropical Forests - Silvetti, Luna Emilce (2025)
(1) Background: Land-use change threatens biodiversity globally, making it essential to anticipate future impacts. (2) Methods: We assess future land-use change scenarios as a tool for analyzing the taxonomic and functional richness of birds in the Serrano forest. We developed two change scenarios: The “Business as usual” scenario assumes that the trend of land-use change observed between 2004 and 2019 will continue without modifications by 2035 and 2050. The “Sustainable” scenario seeks to achieve a sustainable relationship between anthropogenic land-use activities and ecosystem conservation. We created distribution models and derived the potential distribution of the taxonomic and functional richness of forest and understory specialist birds in the change scenarios. (3) Results: The taxonomic and functional richness of both bird groups was strongly affected in the “Business as usual” change scenario, which presented extreme deforestation events, while the “Sustainable” change scenario tended to maintain bird richness over time. We detected areas with a reduction in richness greater than 20% and areas where richness increased due to being distant from urbanization and exotic forests.